Keanekaragaman Jenis – Jenis Tumbuhan Marga Ficus di Pesisir Selatan Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Priskila Kurniawat Ayu; I Wayan Mudita; Nixon Rammang (Wana Lestari, 2023)
South Central Timor Regency, especially the South Coastal part, is an area with a dry climate which is an optimal area for the growth of the genus Ficus. Previous research data shows that on Timor Island there are 25 types of Ficus out of 252 species found in Indonesia. However, this data is not based on the results of field research, but from the results of reviews of other studies. Therefore, the purpose of this study was to identify the types of plants of the Ficus genus found on the South Coast of South Central Timor and determine the level of species diversity. The method used in this study is the exploratory method by exploring each coastal habitat, rivers, rocky hills or steep slopes, agricultural land, settlements and forests. To determine the type of Ficus, it was identified based on the criteria of Berg & Corner (2005) while the level of species diversity was determined based on the Shannon Wiener diversity index. The results showed that on the South Coast of Timor Tengah Selatan there were 956 individuals consisting of 19 species of Ficus and 3 of them namely Ficus callophylla, Ficus drupacea and Ficus microcarpa which had never been reported on the island of Timor. The level of species diversity is included in the moderate category, this is because only a few species dominate.